Empirical Study of the Impact of QFII Shareholdings on Board Governance and Corporate Performances ——Based on Chinese Listed Companies Data. Issue 4 (August 2019) - Ren, Xiaoyan; Yang, Shuili
Abstract: Board governance structure is introduced into this paper as mediating variables to analyze the indirect impact of QFII shareholdings on corporate operating performances. The data of QFII shareholdings ratio between 5% and 30% of Shanghai and Shenzhen A-share listed companies from 2008 to 2016 after the completion of China's split-share structure reform are selected to carry out empirical study. Empirical results indicate that the mediating effects of proportion of foreign directors, separation degree of ownership and management right of board, president and general manager being one person or not, proportion of independent directors and senior managers' shareholdings ratio of board governance structure are significant. However, the mediating effect of the numbers of "four committees" of board is not significant.